2018
DOI: 10.15386/cjmed-972
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Pressure Is More Relevant Than Systolic and Diastolic Blood Pressure in Patients With Type 2 Diabetes and Cardiovascular Disease

Abstract: Background and aimsThe parameters evaluated during 24-hour ambulatory blood pressure monitoring were reported to be predictors of cardiovascular events. We aimed to investigate mean blood pressure, blood pressure variability and pulse pressure during 24-hour ambulatory blood pressure monitoring in type 2 diabetes patients and to establish their relationship with the presence of atherosclerotic cardiovascular disease (CVD).MethodsThe observational study included type 2 diabetes patients randomly selected and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…"A study found that patient with diabetes and hypertensive with coronary artery disease has more pulse pressure compared with the normal population(daytime pulse pressure 56.2±13.1 vs. 50.6±11.3 mmHg, p=0.003; nighttime pulse pressure 56.5±14.2 vs. 50.7±12.4 mmHg, p=0.005; 24-hour pulse pressure 54.7±13.6 vs. 49.0±12.0 mmHg, p=0.003). "Our study also found significant correlation of PP with circadian variability that signifies the need for shifting the focus from systolic and diastolic Bp to assess and risk stratify patients(79).ABPM 24hrsPP, gives correlation with progression of albuminuria (P=0.015 and 0.052, respectively) than ABPM reading and office PP. The adjusted hazards ratio (95% CI) per each 10-mm Hg increment in ambulatory pulse pressure was 1.23(1.04 to 1.42).…”
supporting
confidence: 54%
“…"A study found that patient with diabetes and hypertensive with coronary artery disease has more pulse pressure compared with the normal population(daytime pulse pressure 56.2±13.1 vs. 50.6±11.3 mmHg, p=0.003; nighttime pulse pressure 56.5±14.2 vs. 50.7±12.4 mmHg, p=0.005; 24-hour pulse pressure 54.7±13.6 vs. 49.0±12.0 mmHg, p=0.003). "Our study also found significant correlation of PP with circadian variability that signifies the need for shifting the focus from systolic and diastolic Bp to assess and risk stratify patients(79).ABPM 24hrsPP, gives correlation with progression of albuminuria (P=0.015 and 0.052, respectively) than ABPM reading and office PP. The adjusted hazards ratio (95% CI) per each 10-mm Hg increment in ambulatory pulse pressure was 1.23(1.04 to 1.42).…”
supporting
confidence: 54%
“…Moreover, a study with long-term follow-up revealed that younger and middle-aged adults with idiopathic spontaneous hypertension had a higher relative risk for CVD and congestive heart disease than those with optimal-normal BP ( 9 ). For specific patient groups, such as those with both type 2 diabetes and CVD compared to those without CVD, PP has been shown to be more relevant than systolic and diastolic BP ( 10 ). PP measurement is convenient in routine medical settings, and it might not only provide a quick means of estimating CVD risk but also may have significant clinical value for predicting CVD outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of PP results in more stress in arteries, which leads to increased elastic component fatigue and fracture and weakens the lining of blood vessels [34]. PP is a wellestablished independent predictor of stroke incidence among normotensive individuals [34,35] and was shown to have higher relevance to stroke etiology than SBP and DBP in patients with type 2 diabetes [36]. Among several previous studies on SGLT2i, one study showed that addition of dapagliflozin significantly decreased PP for 8 weeks [37].…”
Section: Discussionmentioning
confidence: 99%